THE IMPORTANCE OF UNDERSTANDING JUNIOR DOCTOR PERCEPTIONS OF CONFIDENCE AND COMPETENCE IN RELATION TO THE FEBRILE CHILD. Issue 12 (23rd November 2015) - Ronald, D; Martin, G; Coats, T; Matheson, D
Abstract : Objectives & Background: It is important to determine whether trainees have gained a greater belief in their abilities at carrying out a particular skill or knowledge set (confidence), whether they are technically more proficient in putting them into practice (competence) or both. If confidence and competence are not clearly understood it cannot be assumed self-reported outcomes during training are valid. The aim of this work was to explore Junior Doctors' understanding of how they perceive their own performance in respect of managing feverish childrenTable 1 . Methods: Junior doctors (postgraduate year 2) in a children's emergency department were consented to take part in the study following ethics committee approval. Two focus group sessions, utilising a novel focus group design (meta-planning) as a methodology to drive discussion, were undertaken one week apart (9 and 7 participants), to maximise attendance and allow unexplored themes to be discussed further if one session was inadequate. A repeat session for a new group (8 participants) was held one year later using the same methodology. Results: The focus groups demonstrated that although the junior doctors recognised a difference between confidence and competence they were not able to define it. Despite this difficulty there was general agreement of feeling 'safe' in the management of the febrile child at the end of the attachment. The groups also struggled to separate collectively themed categories of skills or constructs into distinct competence and confidence domains (figure one). Conclusion: A perception of 'safeness' is as a concept that may aid self-evaluation and we present a matrix (table) that might be used to examine this and its relationship with confidence and competence. This will be useful for clinical supervisors and educators in Children's Emergency Departments as the concept is evolved from management of the febrile child but it is likely to have much wider useFigure 1 .